On the Peculiar Relevance of a Fundamental Dilemma of Minimum-Wage Regulation in Post-Socialism - Apropos of an International Investigation - István R. Gábor (Hungarian Academy of Sciences, Institute of Economics, 2010)
To the extent minimum-wage regulation is effective in fighting against excessive earnings handicaps of those at the bottom of earnings distribution, it may have the side-effect of worsening their employment prospects. A demand-and-supply interpretation of data on the relative employment rate and earnings position of the least educated in the EU27 suggests that the resulting dilemma might be particularly relevant for minimum-wage policies in post-socialist countries.
Keywords: J21; J23; J31; J38; J71; 330; minimum wage; employment; earnings dispersion; demand and supply of labour; wage and employment discrimination; Mindestlohn; Erwerbstätigkeit; Lohnpolitik; EU-Staaten; Transformationsstaaten